Regulating gasoline retail markets: The case of Germany - Nadine Wittmann (Kiel Institute for the World Economy (IfW), 2014)
In 2011, price peaks in retail gasoline prices caused public outrage and attracted the attention of German regulatory agencies. After having examined the market, competition authorities concluded that tacit collusion existed but could not easily be prosecuted under the given competition law. In several other countries, various types of regulatory schemes are implemented to tackle tacit collusive behavior. E.g. there are price ceilings established in Luxembourg or per day limits of price increases given in Austria. However, research has found that none of them has led to satisfactory results. Hence, the following paper proposes a different regulatory approach, i.e. the implementation of corrective taxes. Results show that a special type of variable tax scheme successfully manages to render collusion an unprofitable business. In addition, it is also easy to levy and monitor. Thereby, the inherent vice of the gasoline retail market, i.e. the transparency that enables tacit - and therefore non-prosecutable - collusion, could be turned into a regulatory virtue as it becomes a powerful means to help successfully tackle imperfect competition and to bring about a more efficient market outcome.
Keywords: Q48; D42; D43; 330; gasoline retail market; regulation; market structure and antitrust; collusion